Plasma microRNA Levels Combined with CEA and CA19-9 in the Follow-Up of Colorectal Cancer Patients - Pesta, Martin; Kucera, Radek; Topolcan, Ondrej; Karlikova, Marie; Houfkova, Katerina; Polivka, Jiri; Macanova, Tereza; Machova, Iva; Slouka, David; Kulda, Vlastimil (Cancers, 2019)
Colorectal cancer (CRC) ranks among the most common cancers worldwide. Surgical removal remains the best strategy for treatment of resectable tumors. An important part of caring for patients after surgery is monitoring for early detection of a possible relapse of the disease. Efforts are being made to improve the sensitivity and specificity of routinely used carcinoembryonic antigen (CEA) with the use of additional biomarkers such as microRNAs. The aim of our study was to evaluate the prognostic potential of microRNAs and their use as markers of disease recurrence. The quantitative estimation of CEA, CA19-9, and 22 selected microRNAs (TaqMan Advanced miRNA Assays) was performed in 85 paired (preoperative and postoperative) blood plasma samples of CRC patients and in samples taken during the follow-up period. We have revealed a statistically significant decrease in plasma levels for miR-20a, miR-23a, miR-210, and miR-223a (p = 0.0093, p = 0.0013, p = 0.0392, and p = 0.0214, respectively) after surgical removal of the tumor tissue. A statistically significant relation to prognosis (overall survival; OS) was recorded for preoperative plasma levels of miR-20a, miR-21, and miR-23a (p = 0.0236, p = 0.0316, and p =0.0271, respectively) in a subgroup of patients who underwent palliative surgery. The best discrimination between patients with favorable and unfavorable outcomes was achieved by a combination of CEA, CA19-9 with miR-21, miR-20a, and miR-23a (p < 0.0001). The use of these microRNAs for early disease recurrence detection was affected by a low specificity in comparison with CEA and CA19-9. CEA and CA19-9 had high specificity but low sensitivity. Our results show the benefit of combining currently used standard biomarkers and microRNAs for precise prognosis estimation.
Keywords: colorectal cancer; biomarkers; CEA; CA19-9; recurrence; blood plasma; microRNA